2016
DOI: 10.1136/neurintsurg-2016-012787
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience using the two-stage aspiration technique (TSAT) with proximal flow arrest by a balloon guiding catheter for acute ischemic stroke of the anterior circulation

Abstract: TSAT with proximal flow arrest by a balloon guiding catheter is an effective and safe method to achieve good clinical and angiographic outcomes. This method may reduce ENT in the direct aspiration first-pass thrombectomy (ADAPT) technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Intracranial aspiration with proximal flow arrest by a balloon guiding catheter may also reduce the rate of embolic complications. 18 Other safety parameters were similar between the aspiration and stent retriever groups in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Intracranial aspiration with proximal flow arrest by a balloon guiding catheter may also reduce the rate of embolic complications. 18 Other safety parameters were similar between the aspiration and stent retriever groups in our study.…”
Section: Discussionsupporting
confidence: 69%
“…There is one concern about cerebral ischemia caused by continuous proximal blood flow arrest using balloon occlusion, which has also been reported with the TSAT technique [21]. However, we only adopt this technique in patients with intracranial ICA occlusion, so we do not need to worry about this problem because the vessel is initially occluded and there is no blood supply downstream territory.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the use of distal access catheters in association with SR, which is common in clinical practice, can decrease the distal emboli incidence from 5% to 11% [19]. The use of BGCs can also decrease the incidence of distal emboli [20,21]. Regarding intracranial ICA occlusion, the incidence of distal emboli is as high as 75% in patients who underwent MT with conventional guide catheters [20], but the incidence decreases to 0% when MT is combined with BGCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Several methods have been investigated to increase the effects of recanalization therapy, and proximal blood flow control using a balloon-guiding catheter (BGC) was found to increase the recanalization rate, shorten the procedure time, and prevent embolism of new territory (ENT), being an effective method to improve the outcome. [6][7][8] In addition, it was recently reported that BGC located at a site distal to the main trunk of the internal carotid artery (ICA) improves the recanalization rate and shortens the procedure time compared with proximal placement. 9) At our facility, the combination of 100-cm BGC and 40-cm long sheath has been used as a standard device to reliably place the BGC into a site distal to the ICA after treating a patient in whom a BGC was unable to be placed in the ICA due to an insufficient length, resulting in unsuccessful thrombectomy in 2018.…”
Section: Introductionmentioning
confidence: 99%